Relação de alterações conformacionais da prolil oligopeptidase devido a interação com a α – sinucleína - Santos, Gabriel Silva [UNIFESP] (2019)
Prolyl oligopeptidase (EC 3.4.21.26, POP) is a serine peptidase, involved in the metabolism of neuropeptides and peptide hormones. In vitro and in vivo studies show that POP interacts with alpha synuclein (syn) by accelerating the aggregation of this protein, although when prolyl oligopeptidase is inhibited, syn aggregation is reduced. This mechanism for POP's participation in syn aggregation is totally unknown. The structure of POP does not allow peptides larger than 30 amino acid residues or proteins to reach their active center. Data from the literature show that POP presents an open (catalytic and regulatory domain shift with active center exposure) and a closed (catalytic and regulatory domain approach) conformation. The overall objective of this project was to study this possible "open and close" movement that may occur in POP due to interaction with substrates or inhibitors, and the implication of this conformational change in interaction with alpha synuclein. For this purpose, spectroscopic probes were used, when nearby they have characteristic fluorescence emission, excimer, in order to evaluate the conformational movements of POP and the possible implication of these movements in the interaction with syn. To validate the applied methodology, we used Thimet Oligopeptidase (TOP) a protein widely studied in our research group. The use of TOP provided important data for the use of spectroscopic probes showing that the separation of oligomeric species is fundamental for the analyzes studied here. The proteins with the spectroscopic probes showed activity, indicating that the tertiary structure was not impaired and consequently its function. Probe approximation with increasing guanidine chloride concentration showing probe spacing and excimer disappearance were evaluated. In addition, we evaluated by circular dichroism the POP - syn interaction and the hydrolysis profile of POP in the presence of syn. Interestingly, the high concentration of syn hinders substrate access to the active center, and the interaction between proteins occurs a change in secondary structure